2013
DOI: 10.1111/gcbb.12095
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of nitrogen fixation to first year Miscanthus × giganteus

Abstract: Many characteristics make Miscanthus 9 giganteus an appealing bioenergy feedstock in temperate North America, but the degree to which this plant species interacts with nitrogen-fixing bacteria remains understudied. Demonstration of associative nitrogen fixation in Miscanthus would support management with minimal fertilizer inputs that is demanded of long-term biofuel sustainability. As a first step, we investigate the role of biological nitrogen fixation in nutrition of immature Miscanthus and temporal dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 48 publications
1
58
0
Order By: Relevance
“…The difference in community structure between rhizosphere communities of the two host species is small, though statistically significant. Our previous study (Keymer & Kent, 2014), which demonstrated a 16% contribution from BNF to the nitrogen uptake during the first year of M. 9 giganteus growth, was conducted at Urbanathe site with the highest average soil N content and lowest average nifH abundance. (n = 207 rhizosphere samples, n = 202 for endophytic compartment samples).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The difference in community structure between rhizosphere communities of the two host species is small, though statistically significant. Our previous study (Keymer & Kent, 2014), which demonstrated a 16% contribution from BNF to the nitrogen uptake during the first year of M. 9 giganteus growth, was conducted at Urbanathe site with the highest average soil N content and lowest average nifH abundance. (n = 207 rhizosphere samples, n = 202 for endophytic compartment samples).…”
Section: Discussionmentioning
confidence: 99%
“…Extraction of endophytic community DNA was carried out as described by Keymer & Kent (2014), a modification of the process described by Brulc et al (2009). Adhering rhizosphere soil was eluted from the root surface by vigorously shaking the Nalgene bottles.…”
Section: Sample Processingmentioning
confidence: 99%
See 3 more Smart Citations